Transaminitis in Dengue: A Retrospective Observational Study in an Intensive Care Unit - Kiran Bada Revappa; Murthy N L Narumilli; Pradeep Rangappa; Karthik Rao (Journal of Clinical and Diagnostic Research, 2022)
Introduction: Dengue fever, a frequently encountered arbo viral infection is associated with multiorgan dysfunction in its severe form. The involvement of liver characterised by transaminitis is quite prevalent in such cases admitted to Intensive Care Unit (ICU). Aim: To evaluate the occurrence and severity of transaminitis in dengue patients admitted to the ICU. Also to find the association between transaminitis and other severity predictors of dengue (low platelet count, high packed cell volume and organ dysfunction). Materials and Methods: This retrospective observational study was conducted at Columbia Asia Referral Hospital Yeshwanthpur, Bengaluru, Karnataka, India, from October 2019 to January 2020. Total 80 patients of either sex diagnosed with seropositive dengue were included in the study. The parameters like platelet count, packed cell volume, liver enzymes {Serum Glutamic Pyruvic Transaminase (SGPT) and Serum Glutamic Oxalacetic Transaminase (SGOT)} were recorded and followed-up during the ICU stay. Mean with standard deviation were used to represent quantitative variables whereas description of qualitative variables was done with numbers and percentages. The above variables required application of One way Analysis of Variance (ANOVA), post-hoc Turkey test, Kruskal-Wallis one way ANOVA and Chi-square tests. The differences were considered significant at p-value <0.05. Results: Transaminitis was noted in 96.2% of the total patients. The prevalence of grade 1, 2, 3, 4 transaminitis was 21.2%, 30%, 36.2% and 8.7%, respectively. Mean platelet counts in grade 1, 2, 3 and 4 transaminitis were 19.41±13.17×103/μL, 16.04±11.24×103/μL, and 14.14±5.19×103/μL, and 20.57±10.47×103/μL, respectively. The association between mean platelet counts and grades of transaminitis was not statistically significant (p-value=0.61). Mean Packed Cell Volume (PCV) in patients with grade 1, 2, 3 and 4 transaminitis showed an increasing trend of mean PCV when compared to PCV of 35.67±1.52 in patients with normal SGOT/SGPT levels. The association between different grades of transaminitis and mean PCV values during the course of ICU stay was statistically significant (p-value=0.038). Conclusion: Transaminitis is very common among the dengue patients in ICU and it increases in conjunction with the severity of dengue. It has an association with thrombocytopenia, organ dysfunction and a positive correlation with elevated packed cell volume.